1975
DOI: 10.1161/01.str.6.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bilateral Carotid Artery Ligation on Brain Lactate and Pyruvate Concentrations in Normotensive and Spontaneously Hypertensive Rats

Abstract: Effects of• Brain lactate, pyruvate, and arterial acid-base balance were measured in normotensive rats (NTR) and spontaneously hypertensive rats (SHR) 60 minutes after bilateral carotid artery ligation. Brain lactate and lactate-pyruvate ratios were significantly increased in both SHR and NTR following carotid occlusion, although lactate increase in the former was six and one-half times greater than in the latter. These findings suggest that bilateral carotid occlusion in SHR may cause more severe circulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

1976
1976
1998
1998

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…18 Furthermore, markedly decreased cerebral perfusion pressure after bilateral carotid occlusions in SHR, as represented by lowered carotid back pressure, resulted in ischemic brain energy metabolism 19,20 and ischemic infarction. 21 These changes associated with long-standing hypertension are considered to be major factors for the susceptibility to global cerebral ischemia in SHR.…”
Section: Discussionmentioning
confidence: 99%
“…18 Furthermore, markedly decreased cerebral perfusion pressure after bilateral carotid occlusions in SHR, as represented by lowered carotid back pressure, resulted in ischemic brain energy metabolism 19,20 and ischemic infarction. 21 These changes associated with long-standing hypertension are considered to be major factors for the susceptibility to global cerebral ischemia in SHR.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 throughout the experiment. Our previous studies [7][8][9][10] have demonstrated that The animals were divided into two experimental spontaneously hypertensive rats (SHR) are more sus groups: one for measurements of local CBF and the ceptible to cerebral ischemia than normotensive rats other for determinations of brain tissue metabolites. (NTR) following bilateral carotid occlusion, suggest ing that the cerebral vasoreactivities to changes of the…”
mentioning
confidence: 99%
“…On the other hand, bilateral ligation of the common carotid arteries in spontaneously hypertensive rats (SHR) is known to cause a much greater increase in anaerobic metabolites in the brain 3 and a more severely reduced reactivity of the cortical arterioles to vasodilating agents 4 than in normotensive Wistar rats (NTR), as well as more extensive infarcts in the regions supplied by the carotid artery. 6 These findings suggest that bilateral carotid ligation causes more severe ischemic damages to the brain in SHR.…”
mentioning
confidence: 99%